Pengaruh Implementasi Sistem Informasi Pengelolaan Keuangan Daerah Terhadap Kualitas Laporan Keuangan Pada Pemerintah Kota Palopo - Anwar; Ariandy, Fiar (Insan Cita Bongaya Research Journal, 2021)
This study aims to determine the effect between the implementation of regional financial management information systems and the quality of financial reports in the Palopo City Government. The research method used is a descriptive method using primary data obtained from all SKPD located in Palopo City. The data collection method used is a questionnaire and literature study with a qualitative approach. The analytical tool used in this research is simple regression. The results showed that the implementation of the regional financial management information system had a significant positive effect on the quality of regional financial reports. In the city government of Palopo.